Effect of α-Lipoic Acid on Oxidative Stress in End-Stage Renal Disease Patients Receiving Intravenous Iron. (5th March 2014) - Showkat, Arif; Bastnagel, William R.; Hudson, Joanna Q.
Abstract : Oxidative stress is associated with increased risk of cardiovascular disease in end-stage renal disease (ESRD) patients. Intravenous (IV) iron has been shown to increase oxidative stress. The aim of the study was to evaluate changes in oxidative stress markers following administration of IV sodium ferric gluconate (SFG) to ESRD patients with and without administration of the antioxidant, α -lipoic acid. This is an open-label, crossover study. 125 mg of IV SFG was administered during control (C) and intervention (I) visits. During the I visit, 600 mg of α -lipoic acid was given orally prior to IV SFG. Blood samples were collected at defined time periods for F2 -isoprostane (FIP), lipid hydroperoxide (LHP), malondialdehyde (MDA), and iron indices. We recruited ten African-American ESRD subjects: 50% male; mean age45 ± 9 years; mean hemoglobin13 ± 1 g/dL; ferritin449 ± 145 ng/mL; transferrin saturation27 ± 4 %. There were no significant differences in iron indices between the two visits after IV SFG. MDA, FIP, and LHP increased significantly for both C and I visits with a greater increase in the I group. Administration of IV SFG results in an acute rise in oxidative stress in ESRD patients. In contrast to previous studies, administration of α -lipoic acid was associated with a greater increase in oxidative stress.